Depresión postparto y funcionalidad familiar en mujeres atendidas en el centro de salud universitario de Motupe en la ciudad de Loja - González Salinas, María Belén (2022)
Postpartum depression is a severe affective mental disorder of higher prevalence associated to birth, provoking adverse results in mothers, the baby, their partners and relatives. Disturbed family ambiences reduce the chances of receiving support in stressful situations and increase symptoms of emotional tension. The present research made it possible to know the risk of postpartum depression, determine the family functionality and the relationship between both variables during the posnatal stage among women treated at “Centro de Salud Universitario de Motupe” from the city of Loja. A quantitative, prospective and -of transversal cut- focus was applied, with a sample of 99 healthy women whose ages ranged 15 to 40. 7,1% (n=7) were ≤ 18 years old, the 58,6% (n=58) between19 and 29 years old, and 34,3% (n=34) between 30 and 40 years old, to whom the Edinburgh Posnatal questionnaires along with the Familiar Functionality Scale were applied; 20,2% (n=20) presented risk of developing postpartum depression, 30,3% (n=30) of the women belonged to households with a certain degree of dysfunctionality, besides a reciprocal proportional relationship between the risk of developing postpartum depression and family dysfunctionality was exhibited, with a rate of p= <0,0001, where 15,2% (n=15) of women at risk belonged to households with dysfunctionality. Data similar to the study “Perceived social support and depression levels of women in the postpartum period in Hatay, Turkey” where a connection was found between the risk of depression and family support P <0.001